2015
DOI: 10.1016/j.cmi.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the incidence of Escherichia coli bloodstream infection: variation with region and place of onset

Abstract: Previous research has shown that Escherichia coli infection rates peak in the summer; however, to date there has been no investigation as to whether this is seen in both hospital and community-onset cases, and how this differs across regions. We investigated and quantified E. coli bloodstream infection (BSI) seasonality. A generalized additive Poisson model was fitted to mandatory E. coli BSI surveillance data reported in England. There was no impact of seasonality in hospital-onset cases; however, for the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 11 publications
5
18
1
Order By: Relevance
“…Mandatory surveillance of E. coli bacteraemia was implemented in June 2011 hence long-term trends over time have not been fully established; however the rise in incidence across the two years has mirrored the year-on-year increase in incidence seen in the voluntary surveillance dataset. The results presented here, along with an emerging body of evidence, suggest that there is seasonal variation in E. coli bacteraemia rates, with a peak during the summer [14,15]. …”
Section: Discussionmentioning
confidence: 92%
“…Mandatory surveillance of E. coli bacteraemia was implemented in June 2011 hence long-term trends over time have not been fully established; however the rise in incidence across the two years has mirrored the year-on-year increase in incidence seen in the voluntary surveillance dataset. The results presented here, along with an emerging body of evidence, suggest that there is seasonal variation in E. coli bacteraemia rates, with a peak during the summer [14,15]. …”
Section: Discussionmentioning
confidence: 92%
“…Epidemiological studies in diabetes have demonstrated that hypoglycaemic episodes are more common during summer months, whilst hyperglycaemic complications are more common in the first months of the year, with said patterns ascribed to changes in calorie consumption and physical activity . Increased incidence of Gram‐negative bacteraemia has been reported in summer months and associated with elevated monthly outdoor temperatures . Community acquired pneumonia in contrast is more common in the spring and winter, as a result of the combination of circulating respiratory bacteria being more prevalent during colder seasons, and people spending more time indoors during colder months .…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Increased incidence of Gramnegative bacteraemia has been reported in summer months and associated with elevated monthly outdoor temperatures. [44][45][46] Community acquired pneumonia in contrast is more common in the spring and are more likely to be admitted with significant trauma during winter months, because of an increase in falls and accidents relating to ice/ snow. 49 It is likely that each of these aforementioned diseases influence the seasonal variation in AKI and further studies are required focusing on the precipitating factors which lead to AKI to provide a robust link between disease aetiology and the seasonal variation that we have described.…”
Section: Discussionmentioning
confidence: 99%
“…In England, the seasonality of E. coli BSIs varied by region [32]. As the urinary tract has been reported to be a primary source of infection for BSIs, the seasonality of UTIs could also vary by region.…”
Section: Findings In Contextmentioning
confidence: 99%